2000
DOI: 10.1063/1.372673
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of as-deposited Fe–Al–O alloy films

Abstract: The magnetic and structural properties of as-sputtered nanocrystalline Fe–Al–O films, fabricated by a magnetron sputtering apparatus, are investigated as a function of the sputtering input power and the contents of Al and oxygen. A nanocrystalline Fe88.5Al3.5O8.0 film is found to have 4πMs of 18.2 kG, Hc of 0.6 Oe, μeff of 4600 up to 100 MHz. These excellent soft magnetic properties and high frequency characteristics result from nanocrystalline structure, high electrical resistivity, and moderate anisotropy fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Figure 6 shows the fatigue endurance properties after 10V, 100 us width and 1 ms interval cycles. This fatigue behavior was caused by function of oxide electrodes as a sink for oxygen vacancies 5,10) . In previous study, it is clearly revealed that oxide electrodes can improve the film fatigue resistance 11,12) When the cycling voltage was 10 V, PLZT capacitors with Pt top electrodes showed significant degradation of polarization after 10 4 cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 shows the fatigue endurance properties after 10V, 100 us width and 1 ms interval cycles. This fatigue behavior was caused by function of oxide electrodes as a sink for oxygen vacancies 5,10) . In previous study, it is clearly revealed that oxide electrodes can improve the film fatigue resistance 11,12) When the cycling voltage was 10 V, PLZT capacitors with Pt top electrodes showed significant degradation of polarization after 10 4 cycles.…”
Section: Resultsmentioning
confidence: 99%
“…Among the various metallization processes, electroless metal plating is probably a preferred way to produce metal-coated fabrics due to the attractable advantages such as uniformity of coverage, excellent conductivity, the possibility of metallizing nonconductors, and flexibility [1]. In the previous investigation, the properties of electromagnetic shielding of electroless Ni-, Cu-and Ag-plated fabrics were extensively studied [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%